Active learning effects on students’ performance: A methodological proposal combining cooperative approaches towards improving hard and soft skills - Bressane, Adriano [UNESP]; dos Santos Bardini, Vivian Silveira [UNESP]; Spalding, Marianne [UNESP] (Inderscience Publishers, 2021)
Empirical evidences on the benefits of cooperative learning at the higher education a still limited. This paper aims at verifying the hypothesis of improvement from the cooperative learning to students’ performance. Firstly, the Fast-300 based learning is introduced as a methodological proposal combining cooperative approaches. From a case study, analysis of variance was carried out comparing scores, before and after the application of Fast-300. Moreover, students’ perception of effect on theoretical understanding, communication, logical reasoning, and leadership, were collected using Likert-type scale. Then, an index was generated to measure the effect based on this perception. The results showed that the students’ performance after the application of Fast-300 had a statistically significant improvement. In addition, the students’ perception indicated enhancement of the skills evaluated. In conclusion, the Fast-300 can be considered a promising alternative for improving both hard and soft-skills. Future studies may evaluate the effects on cognitive permanence, emotional effects, among other skills.
Keywords: 21st-century skills; Educational research; Engineering education; Fast-300 method; Higher education; Innovative education; Student engagement; Student skill; Studentcentred learning; TBL method